Mitonuclear Genetic Interactions in the Basidiomycete Heterobasidion parviporum Involve a Non-conserved Mitochondrial Open Reading Frame - Clergeot, Pierre-Henri; Olson, Åke (Frontiers in Fungal Biology, 2021)
The mitochondrial and nuclear genomes of Eukaryotes are inherited separately and consequently follow distinct evolutionary paths. Nevertheless, the encoding of many mitochondrial proteins by the nuclear genome shows the high level of integration they have reached, which makes mitonuclear genetic interactions all the more conceivable. For each species, natural selection has fostered the evolution of coadapted alleles in both genomes, but a population-wise divergence of such alleles could lead to important phenotypic variation, and, ultimately, to speciation. In this study in the Basidiomycete Heterobasidion parviporum, we have investigated the genetic basis of phenotypic variation among laboratory-designed heterokaryons carrying the same pair of haploid nuclei, but a different mitochondrial genome. Radial growth rate data of thirteen unrelated homokaryotic parents and of their heterokaryotic offspring were combined with SNP data extracted from parental genome sequences to identify nuclear and mitochondrial loci involved in mitonuclear interactions. Two nuclear loci encoding mitochondrial proteins appeared as best candidates to engage in a genetic interaction affecting radial growth rate with a non-conserved mitochondrial open reading frame of unknown function and not reported apart from the Russulales order of Basidiomycete fungi. We believe our approach could be useful to investigate several important traits of fungal biology where mitonuclear interactions play a role, including virulence of fungal pathogens.